PENERAPAN METODE EDUTAINMENT TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN MATEMATIKA DI SD NEGERI 49/VII LADANG PANJANG - Yati Sri Dewi; Nor Ainun; Siti Rapita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning methods are very necessary because everything related to the learning process certainly uses methods in its delivery, the use of the right method can also determine student learning outcomes. The application of the edutainment method aims to provide convenience to students, create a conducive learning environment, a tool to reduce boredom and can help improve student learning outcomes. This research was conducted on mathematics subjects because mathematics is one of the most important subjects among other subjects, has an important role in various disciplines and advances human thinking power, and is very useful for everyday life. This research is included in Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of three meetings. One cycle consists of 4 stages of activity, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The data collection technique used in this study is qualitative and quantitative data analysis. The results of this study indicate that student learning outcomes after implementing the edutainment method have increased, this can be seen from the learning outcomes of students in cycle I, students who have an average score of 0-54-55-59 (very low, low) none, 60-79 as many as 7 students, 80-89 (high) as many as 18 students, and those who have an average score of 90-100 (very high) as many as 6 students. And in cycle II, students who have an average score of 0-54-55-59 (very low, low) none, 60-79 as many as 12 students, while students who have an average score of 80-89 (high) as many as 15 students, while those who have an average score of 90-100 (very high) as many as 4 students.